Use of Plant-Based Coagulants Sorghum Bicolor and Trifolium Repens as Future Alternatives for Textile Wastewater Treatment Based on Computational Model (Journal of Global Humanities and Social Sciences, 2024)
Sorghum bicolor and Trifolium repens extracts as plant coagulants can be used for wastewater treatment instead of chemical coagulants. This study investigates the effects of pH and coagulant dose on COD and turbidity reduction by natural coagulants. In the optimum treatment conditions of 100 mg/L coagulant dose and pH 7, high turbidity (81.34%), and COD reduction (62%) (compared with alum and FeCl3) were obtained. The percentage of COD reduction is higher in Trifolium repens than the other plant coagulant, and the percentage of turbidity reduction is higher in Sorghum bicolor. FT-IR spectra were performed on the plant extracts to identify the existing factors in active extracts. Also, outlet COD and turbidity values can be predicted and calculated according to computational equation in similar treatment systems. It should be mentioned that the only applied solvent for extracting the natural coagulant seeds was distilled water, and none of the other solvents such as NaCl and NaOH were used. According to the results, the characteristics of the treated effluents by the plant extracts make them appropriate alternatives for textile wastewater treatment.